Preparation method of fuel cell catalyst

By preparing the carrier as a ternary alloy catalyst for pretreatment of mesoporous carbon and titanium dioxide, doping P and Co to improve the electronic structure, the existing catalysts have been solved with low activity and complex synthesis conditions, high activity and stability are achieved, and cost is reduced.

CN119852428AActive Publication Date: 2025-04-18SHANGHAI JIPING NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202510076650.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The catalytic activity of existing fuel cell catalysts is low, the synthesis conditions are complex, and the utilization rate of metal particles is low.

Method used

By preparing a ternary alloy catalyst, including the carrier being pretreated mesoporous carbon and titanium dioxide, and by doping P and Co, the electronic structure and energy band structure of titanium dioxide are improved and catalytic activity is improved.

Benefits of technology

High catalytic activity is achieved, the stability of the catalyst and the reliability of the system are improved, while reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005247297010000091
    Figure BDA0005247297010000091
  • Figure BDA0005247297010000101
    Figure BDA0005247297010000101
Patent Text Reader

Abstract

The invention relates to a preparation method of a fuel cell catalyst, and belongs to the technical field of catalysts. According to the invention, the carrier is mixed with the metal salt and then subjected to a hydrogen reduction process to obtain the ternary alloy catalyst which can be used for the fuel cell catalyst, and the catalyst takes platinum as a main component and cobalt and palladium as auxiliary components, so that both the performance and the stability of the catalyst can be ensured; wherein Co can modify the crystal face structure of Pt, the active point location of Pt and the activity of the catalyst are improved, and the catalytic activity is higher. The catalyst can resist chemical corrosion and physical wear in the reaction process by optimizing element composition and a microstructure, long-term catalytic activity is kept, and the reliability and stability of a system are improved. In addition, as Co and Pd are cheaper than Pt, the cost of the catalyst is lower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts and relates to a method for preparing a fuel cell catalyst. Background Art

[0002] Fuel cells convert the chemical energy of fuel and oxidant into electrical energy through electrochemical reactions. When the fuel is hydrogen and the oxidant is oxygen, the reaction only produces water, accompanied by the loss of some heat. Compared with thermal generators, fuel cells have the advantages of high efficiency, no environmental pollution, and unlimited sources of reactants.

[0003] The development of electrode catalysts is an indispensable part of the research and development of fuel cell systems. Together with ion electrolyte membranes and bipolar plates, they constitute the three key materials of fuel cell systems. The most common ones are Pt-based catalysts. Pt nanocrystalline catalysts are the most effective catalysts for catalyzing oxygen reduction reactions (ORR), but for oxygen evolution reactions (OER), the catalytic activity of Pt nanocrystals is poor, which limits their widespread use. It is also worth noting that the synthesis conditions of catalysts with special alloy nanostructures with high activity are generally more complicated. At the same time, the utilization rate of catalyst metal particles in the prior art is low, and the catalytic activity is poor.

[0004] Therefore, it is necessary to develop a new alloy catalyst with high catalytic activity that can be used in fuel cells. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a fuel cell catalyst. The catalyst prepared by the present invention has excellent catalytic activity.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a fuel cell catalyst comprises the following steps:

[0008] S1. Mesoporous carbon pretreatment:

[0009] Disperse the mesoporous carbon in a nitric acid solution, stir and treat at 80-95°C for 6-12h, filter and obtain a solid after stirring, rinse the solid with deionized water for 3 times and then wash it to neutrality to obtain pretreated mesoporous carbon, wherein the amount ratio of the mesoporous carbon to the nitric acid solution is 10mg:1mL;

[0010] S2. Vector preparation:

[0011] S2.1. Mix NaH2PO2·H2O and titanium dioxide in a mass ratio of 20:3, grind at a speed of 400 r / min for 3 hours to obtain a solid powder, then place the solid powder in a tube furnace, calcine at 450-550°C for 1-2 hours under an argon atmosphere, continue to heat up to 700°C for 2-3 hours, naturally cool to room temperature after calcination, wash with deionized water and ethanol in turn, and then dry in a vacuum oven at 40°C for 12-16 hours to obtain pretreated titanium dioxide;

[0012] S2.2, mixing the pretreated titanium dioxide and the pretreated mesoporous carbon in a mass ratio of 1:2 by ball milling to obtain solid A;

[0013] S2.3, dispersing solid A in HCl solution, ultrasonically treating for 30 to 60 min, adding pyrrole in an ice bath, and continuing ultrasonic treatment for 20 to 35 min to obtain solution A, wherein the amount ratio of pretreated mesoporous carbon, HCl solution and pyrrole in solution A is 2 g: 800 mL: 1 mL;

[0014] S2.4, adding ammonium persulfate to the HCl solution, ultrasonically treating for 20 to 30 minutes at room temperature to obtain solution B, mixing solutions A and B in a volume ratio of 2:1, stirring at a speed of 400 r / min for 3 to 6 hours, filtering after the stirring, washing the obtained product with ethanol and deionized water, freeze-drying to obtain solid B, heating solid B to 650 to 800°C under a nitrogen atmosphere, roasting for 2 to 3 hours, and then naturally cooling to room temperature to obtain the carrier;

[0015] S3. Preparation of fuel cell catalyst:

[0016] S3.1, adding the carrier into ethylene glycol, stirring, and obtaining dispersion 1;

[0017] S3.2. Then dissolve cobalt nitrate, palladium chloride and platinum nitrate in deionized water to obtain a salt solution, wherein the concentration of cobalt nitrate in the salt solution is 10 mmol / L, the concentration of palladium chloride is 10 mmol / L, and the concentration of platinum nitrate is 20 mmol / L, and mix the salt solution with dispersion 1 in a volume of 2:1, adjust the pH of the mixed solution to 7-8 with ammonia water, heat until the water is completely evaporated, first heat at 150°C under vacuum conditions for 1 h, then heat treat at 300-500°C in a hydrogen atmosphere for 4-6 h, then calcine at 700-750°C under argon protection for 1-2 h, and naturally cool to room temperature to obtain the fuel cell catalyst.

[0018] As a preferred technical solution of the present invention, in step S1, the concentration of nitric acid is 5 mol / L.

[0019] As a preferred technical solution of the present invention, in step S2.2, the ball milling condition is grinding at a rotation speed of 400 r / min for 3 to 5 hours.

[0020] As a preferred technical solution of the present invention, in step S2.3, the concentration of the HCl solution is 1 mol / L.

[0021] As a preferred technical solution of the present invention, in step S2.4, the usage ratio of ammonium persulfate to HCl solution in solution B is 1 g:1 L.

[0022] As a preferred technical solution of the present invention, in step S2.4, the heating rate during heating under the nitrogen atmosphere is 8°C / min.

[0023] As a preferred technical solution of the present invention, in step S2.4, the concentration of the HCl solution is 1 mol / L.

[0024] As a preferred technical solution of the present invention, in step S2.4, the freeze-drying condition is freeze-drying at -60°C for 12 hours.

[0025] As a preferred technical solution of the present invention, in step S3.1, the usage ratio of the carrier to ethylene glycol in the dispersion 1 is 4 mg:5 mL.

[0026] As a preferred technical solution of the present invention, in step S3.2, the heating temperature is 90°C.

[0027] The present invention prepares a ternary alloy catalyst for a fuel cell, comprising a carrier and an active metal, wherein the carrier is mesoporous carbon and titanium dioxide is treated, and titanium dioxide and sodium hypophosphite are calcined in an Ar gas atmosphere to obtain P-doped titanium dioxide. The electronic structure and energy band structure of titanium dioxide can be changed by doping, thereby improving its catalytic activity. The doping element may provide additional electrons or holes to promote charge transfer in the catalytic reaction. When titanium dioxide is used as a carrier of a platinum-based catalyst, doping further enhances the interaction between platinum and titanium dioxide, thereby improving the overall performance of the catalyst.

[0028] Mixing pretreated titanium dioxide with oxidized mesoporous carbon, and doping titanium dioxide in the mesoporous carbon carrier can improve the electron transport performance of the mesoporous carbon, reduce the recombination of electrons and holes, and thus improve the conductivity and electrochemical properties of the overall material. Titanium dioxide has high chemical and thermal stability, and after doping, it can enhance the stability of the mesoporous carbon carrier, so that it can maintain good performance in various environments. This mixed carrier is closely combined with the catalyst particles through physical or chemical effects to form a strong catalyst-carrier interface, which enhances the adhesion and stability of the catalyst.

[0029] The obtained solid A is polymerized and carbonized by pyrrole, and polypyrrole is carbonized and doped on the surface of solid A. Polypyrrole is coated on the outside of solid A. While improving the dispersion of the carrier by strengthening the support effect, it also helps to increase the interaction between the carrier and the active metal, thereby effectively improving the activity and inhibiting the oxidation corrosion of the carbon carrier. Polypyrrole generates electron transfer with the carrier surface through conjugation, adjusting the outer electronic structure of the carbon carrier.

[0030] Beneficial effects of the present invention:

[0031] In the present invention, a ternary alloy catalyst that can be used as a fuel cell catalyst is obtained by mixing the carrier with a metal salt and then performing a hydrogen reduction process. In the present invention, the catalyst is mainly platinum, and cobalt and palladium are supplementary, which can ensure that the performance and stability of the catalyst are taken into account. Among them, Co can modify the crystal surface structure of Pt, improve the active sites of Pt and the activity of the catalyst, and the catalytic activity is higher. By optimizing the elemental composition and microstructure, the catalyst can resist chemical corrosion and physical wear during the reaction process, maintain long-term catalytic activity, and improve the reliability and stability of the system. In addition, since the prices of Co and Pd are lower than Pt, the cost of the present invention is lower. DETAILED DESCRIPTION

[0032] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0033] The mesoporous carbon of the present invention is CMK-3; NaH2PO2·H2O: purchased from Tianjin Xiensi Biochemical Technology Co., Ltd., product number: S-36670; titanium dioxide: purchased from Shanghai McLean Biochemical Technology Co., Ltd., product number: T832270; pyrrole: purchased from Shanghai Bangcheng Chemical Co., Ltd.; ammonium persulfate: purchased from Shanghai Yien Chemical Technology Co., Ltd., product number: R052157; cobalt nitrate: purchased from Shanghai Yien Chemical Technology Co., Ltd.; palladium chloride: purchased from Tianjin Xiensi Biochemical Technology Co., Ltd., product number: P-59032; platinum nitrate: purchased from Shanghai McLean Biochemical Technology Co., Ltd., product number: P799309.

[0034] Example 1

[0035] S1. Mesoporous carbon pretreatment:

[0036] The mesoporous carbon was dispersed in a nitric acid solution with a concentration of 5 mol / L, and stirred at 80°C for 6 hours. After stirring, the solid was filtered to obtain a solid. The solid was washed with deionized water for 3 times and then washed to neutrality to obtain the pretreated mesoporous carbon, wherein the amount ratio of the mesoporous carbon to the nitric acid solution was 10 mg: 1 mL;

[0037] S2. Vector preparation:

[0038] S2.1. Mix NaH2PO2·H2O and titanium dioxide in a mass ratio of 20:3, grind at a speed of 400 r / min for 3 hours to obtain a solid powder, then place the solid powder in a tube furnace, calcine at 450°C for 1 hour under an argon atmosphere, continue to heat up to 700°C for 2 hours, naturally cool to room temperature after calcination, wash with deionized water and ethanol in turn, and then dry in a vacuum oven at 40°C for 12 hours to obtain pretreated titanium dioxide;

[0039] S2.2, grinding the pretreated titanium dioxide and the pretreated mesoporous carbon in a mass ratio of 1:2 by a ball mill at a speed of 400 r / min for 3 h to obtain solid A;

[0040] S2.3, dispersing solid A in 1 mol / L HCl solution, ultrasonically treating for 30 min, adding pyrrole in an ice bath, and continuing ultrasonic treatment for 20 min to obtain solution A, wherein the amount ratio of pretreated mesoporous carbon, HCl solution and pyrrole in solution A is 2 g: 800 mL: 1 mL;

[0041] S2.4. Add ammonium persulfate to a 1 mol / L HCl solution, and perform ultrasonic treatment at room temperature for 20 min to obtain solution B, wherein the amount ratio of ammonium persulfate to HCl solution in the solution B is 1 g:1 L; mix solutions A and B at a volume ratio of 2:1, and stir at a speed of 400 r / min for 3 h. After stirring, filter, wash the obtained product with ethanol and deionized water, and freeze-dry at -60°C for 12 h to obtain solid B. Heat solid B to 650°C at a heating rate of 8°C / min under a nitrogen atmosphere, roast for 2 h, and then naturally cool to room temperature to obtain the carrier;

[0042] S3. Preparation of fuel cell catalyst:

[0043] S3.1. Add the carrier to ethylene glycol and stir to obtain dispersion 1. The ratio of the carrier to ethylene glycol is 4 mg:5 mL.

[0044] S3.2. Then dissolve cobalt nitrate, palladium chloride and platinum nitrate in deionized water to obtain a salt solution, wherein the concentration of cobalt nitrate in the salt solution is 10 mmol / L, the concentration of palladium chloride is 10 mmol / L, and the concentration of platinum nitrate is 20 mmol / L, and mix the salt solution with dispersion 1 in a volume of 2:1, adjust the pH of the mixed solution to 7-8 with ammonia water, heat to 90°C to evaporate the water completely, first heat at 150°C under vacuum conditions for 1 hour, then heat treat at 300°C in a hydrogen atmosphere for 6 hours, then calcine at 700°C under argon protection for 1 hour, and naturally cool to room temperature to obtain the fuel cell catalyst.

[0045] Example 2

[0046] S1. Mesoporous carbon pretreatment:

[0047] The mesoporous carbon was dispersed in a nitric acid solution with a concentration of 5 mol / L, and stirred at 90°C for 9 hours. After stirring, the solid was filtered to obtain a solid. The solid was washed with deionized water for 3 times and then washed to neutrality to obtain the pretreated mesoporous carbon, wherein the amount ratio of the mesoporous carbon to the nitric acid solution was 10 mg: 1 mL;

[0048] S2. Vector preparation:

[0049] S2.1. Mix NaH2PO2·H2O and titanium dioxide in a mass ratio of 20:3, grind at a speed of 400 r / min for 3 h to obtain a solid powder, then place the solid powder in a tube furnace, calcine at 500°C for 1.5 h under an argon atmosphere, continue to heat up to 700°C for 2.5 h, naturally cool to room temperature after calcination, wash with deionized water and ethanol in turn, and then dry in a vacuum oven at 40°C for 14 h to obtain pretreated titanium dioxide;

[0050] S2.2, grinding the pretreated titanium dioxide and the pretreated mesoporous carbon in a mass ratio of 1:2 by a ball mill at a speed of 400 r / min for 4 h to obtain solid A;

[0051] S2.3, dispersing solid A in 1 mol / L HCl solution, ultrasonically treating for 40 min, adding pyrrole in an ice bath, and continuing ultrasonic treatment for 30 min to obtain solution A, wherein the amount ratio of pretreated mesoporous carbon, HCl solution and pyrrole in solution A is 2 g: 800 mL: 1 mL;

[0052] S2.4, adding ammonium persulfate to a 1 mol / L HCl solution, and subjecting the solution to ultrasonic treatment for 25 min at room temperature to obtain a solution B, wherein the amount ratio of ammonium persulfate to HCl solution in the solution B is 1 g:1 L; mixing solutions A and B at a volume ratio of 2:1, stirring at a speed of 400 r / min for 5 h, filtering after stirring, washing the obtained product with ethanol and deionized water, freeze-drying at -60°C for 12 h to obtain a solid B, heating the solid B to 700°C at a heating rate of 8°C / min under a nitrogen atmosphere, roasting for 2.5 h, and then naturally cooling to room temperature to obtain the carrier;

[0053] S3. Preparation of fuel cell catalyst:

[0054] S3.1. Add the carrier to ethylene glycol and stir to obtain dispersion 1. The ratio of the carrier to ethylene glycol is 4 mg:5 mL.

[0055] S3.2. Then dissolve cobalt nitrate, palladium chloride and platinum nitrate in deionized water to obtain a salt solution, wherein the concentration of cobalt nitrate in the salt solution is 10 mmol / L, the concentration of palladium chloride is 10 mmol / L, and the concentration of platinum nitrate is 20 mmol / L, and mix the salt solution with dispersion 1 in a volume of 2:1, adjust the pH of the mixed solution to 7-8 with ammonia water, heat to 90°C to evaporate the water completely, first heat at 150°C under vacuum conditions for 1 h, then heat treat at 400°C in a hydrogen atmosphere for 5 h, then calcine at 730°C under argon protection for 1.5 h, and naturally cool to room temperature to obtain the fuel cell catalyst.

[0056] Example 3

[0057] S1. Mesoporous carbon pretreatment:

[0058] The mesoporous carbon was dispersed in a nitric acid solution with a concentration of 5 mol / L, and stirred at 95°C for 12 h. After stirring, the solid was filtered to obtain a solid. The solid was washed with deionized water for 3 times and then washed to neutrality to obtain the pretreated mesoporous carbon, wherein the amount ratio of the mesoporous carbon to the nitric acid solution was 10 mg: 1 mL;

[0059] S2. Vector preparation:

[0060] S2.1. Mix NaH2PO2·H2O and titanium dioxide in a mass ratio of 20:3, grind at a speed of 400 r / min for 3 hours to obtain a solid powder, then place the solid powder in a tube furnace, calcine at 550°C for 2 hours under an argon atmosphere, continue to heat up to 700°C for 3 hours, naturally cool to room temperature after calcination, wash with deionized water and ethanol in turn, and then dry in a vacuum oven at 40°C for 16 hours to obtain pretreated titanium dioxide;

[0061] S2.2, grinding the pretreated titanium dioxide and the pretreated mesoporous carbon in a mass ratio of 1:2 by a ball mill at a speed of 400 r / min for 5 h to obtain solid A;

[0062] S2.3, dispersing solid A in 1 mol / L HCl solution, ultrasonically treating for 60 min, adding pyrrole in an ice bath, and continuing ultrasonic treatment for 35 min to obtain solution A, wherein the amount ratio of pretreated mesoporous carbon, HCl solution and pyrrole in solution A is 2 g: 800 mL: 1 mL;

[0063] S2.4, adding ammonium persulfate to a 1 mol / L HCl solution, and subjecting the solution to ultrasonic treatment for 30 min at room temperature to obtain a solution B, wherein the amount ratio of ammonium persulfate to HCl solution in the solution B is 1 g:1 L; mixing solutions A and B at a volume ratio of 2:1, stirring at a speed of 400 r / min for 6 h, filtering after stirring, washing the obtained product with ethanol and deionized water, freeze-drying at -60°C for 12 h to obtain a solid B, heating the solid B to 800°C at a heating rate of 8°C / min under a nitrogen atmosphere, roasting for 3 h, and then naturally cooling to room temperature to obtain the carrier;

[0064] S3. Preparation of fuel cell catalyst:

[0065] S3.1. Add the carrier to ethylene glycol and stir to obtain dispersion 1. The ratio of the carrier to ethylene glycol is 4 mg:5 mL.

[0066] S3.2. Then dissolve cobalt nitrate, palladium chloride and platinum nitrate in deionized water to obtain a salt solution, wherein the concentration of cobalt nitrate in the salt solution is 10 mmol / L, the concentration of palladium chloride is 10 mmol / L, and the concentration of platinum nitrate is 20 mmol / L, and mix the salt solution with dispersion 1 in a volume of 2:1, adjust the pH of the mixed solution to 7-8 with ammonia water, heat to 90°C to evaporate the water completely, first heat at 150°C under vacuum conditions for 1 h, then heat treat at 500°C in a hydrogen atmosphere for 4 h, then calcine at 750°C under argon protection for 1 h, and naturally cool to room temperature to obtain the fuel cell catalyst.

[0067] Comparative Example 1

[0068] The difference between Comparative Example 1 and Example 1 is that no pretreated silica is added during the carrier preparation process in Comparative Example 1, and the other operations are the same.

[0069] Comparative Example 2

[0070] The difference between Comparative Example 2 and Example 1 is that steps S2.3 and S2.4 are not performed in Comparative Example 2, and the remaining operations are the same.

[0071] Comparative Example 3

[0072] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, the carrier is only mesoporous carbon without any treatment, and the other operations are the same.

[0073] Performance Test:

[0074] The catalyst, proton conductor polymer and solvent prepared in the embodiment and comparative example are mixed and dispersed to form a catalyst layer ink. The catalyst layer ink is directly sprayed onto the surface of the proton membrane by direct spraying to form thin cathode and anode catalyst layers on the membrane. Then, the diffusion layer is covered on the outside of the cathode catalyst layer and the anode catalyst layer by hot pressing to obtain a fuel cell membrane electrode. The fuel cell membrane electrode is assembled into a single cell, and a cyclic voltammetry curve test is performed to obtain the electrochemical active area of ​​the catalyst. The experimental conditions are: the scanning interval is 0.01-1.15V, and the scanning speed is 20mV / s; the linear scanning voltammetry curve test experimental conditions are: the scanning interval is 0.2-1.0V, the scanning speed is 5mV / s, and the RDE rotation speed is 1600rpm. The obtained data are shown in Table 1 below:

[0075] Table 1

[0076]

[0077]

[0078] According to the above data, it can be seen that the catalyst prepared by the present invention has high catalytic activity.

[0079] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a fuel cell catalyst, characterized in that: The method comprises the following preparation steps: S1. Mesoporous carbon pretreatment: Disperse the mesoporous carbon in a nitric acid solution, stir and treat at 80-95°C for 6-12h, filter and obtain a solid after stirring, rinse the solid with deionized water for 3 times and then wash it to neutrality to obtain pretreated mesoporous carbon, wherein the amount ratio of the mesoporous carbon to the nitric acid solution is 10mg:1mL; S2. Vector preparation: S2.

1. Mix NaH2PO2·H2O and titanium dioxide in a mass ratio of 20:3, grind at a speed of 400 r / min for 3 hours to obtain a solid powder, then place the solid powder in a tube furnace, calcine at 450-550°C for 1-2 hours under an argon atmosphere, continue to heat up to 700°C for 2-3 hours, naturally cool to room temperature after calcination, wash with deionized water and ethanol in turn, and then dry in a vacuum oven at 40°C for 12-16 hours to obtain pretreated titanium dioxide; S2.2, mixing the pretreated titanium dioxide and the pretreated mesoporous carbon in a mass ratio of 1:2 by ball milling to obtain solid A; S2.3, dispersing solid A in HCl solution, ultrasonically treating for 30 to 60 min, adding pyrrole in an ice bath, and continuing ultrasonic treatment for 20 to 35 min to obtain solution A, wherein the amount ratio of pretreated mesoporous carbon, HCl solution and pyrrole in solution A is 2 g: 800 mL: 1 mL; S2.4, ammonium persulfate was added to the HCl solution, and the solution was ultrasonically treated for 20 to 30 minutes at room temperature to obtain solution B, and solutions A and B were mixed in a volume ratio of 2:1, and stirred at a speed of 400 r / min for 3 to 6 hours. After the stirring, the product was filtered, washed with ethanol and deionized water, and freeze-dried to obtain solid B. Solid B was heated to 650 to 800°C in a nitrogen atmosphere, roasted for 2 to 3 hours, and then naturally cooled to room temperature to obtain solid C; S3. Preparation of fuel cell catalyst: S3.1, adding the carrier into ethylene glycol, stirring, and obtaining dispersion 1; S3.

2. Then, cobalt nitrate, palladium chloride and platinum nitrate are dissolved in deionized water to obtain a salt solution, wherein the concentration of cobalt nitrate in the salt solution is 10 mmol / L, the concentration of palladium chloride is 10 mmol / L, and the concentration of platinum nitrate is 20 mmol / L, and the salt solution is mixed with dispersion 1 in a volume of 2:1, and the pH of the mixed solution is adjusted to 7-8 with ammonia water. After heating until the water is completely evaporated, it is first heated at 150°C under vacuum conditions for 1 hour, and then heat-treated at 300-500°C in a hydrogen atmosphere for 4-6 hours, and naturally cooled to room temperature to obtain the fuel cell catalyst.

2. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step S1, the concentration of nitric acid is 5 mol / L.

3. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step S2.2, the ball milling condition is grinding at a rotation speed of 400 r / min for 3 to 5 hours.

4. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step S2.3, the concentration of the HCl solution is 1 mol / L.

5. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step S2.4, the dosage ratio of ammonium persulfate to HCl solution in solution B is 1 g:1 L.

6. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step S2.4, the heating rate during heating under the nitrogen atmosphere is 8°C / min.

7. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step S2.4, the concentration of the HCl solution is 1 mol / L.

8. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step S2.4, the freeze-drying condition is freeze-drying at -60°C for 12 hours.

9. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step S3.1, the ratio of the carrier to ethylene glycol in the dispersion 1 is 4 mg:5 mL.

10. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step S3.2, the heating temperature is 90°C.

Citation Information

Patent Citations

  • Method for preparing iron-carrying ordered mesoporous carbon materials

    CN101580240A

  • Battery cathode catalyst, preparation method of battery cathode catalyst, battery cathode film and metal air battery

    CN109461943A

  • Method for forming platinum group noble metal catalyst layer on surface of nickel textile net

    CN118910649A

  • Electrode for fuel cell having high durability, method for manufacturing same, and membrane-electrode assembly comprising same

    US20220263108A1

Cited By

  • Crystal face optimization and gas phase synthesis system and method for ultra-low platinum loading catalyst

    CN121466951A